Prevalence of ocular morbidities of children in higher primary schools in rural areas of Mangalore - R., Vidya; Kiran, K.G. (International Journal Of Community Medicine And Public Health, 2017)
Background: Vision plays an important role in proper growth of a child, as poor vision can lead to reduction in the learning potential of a child. Various causes can bring about poor vision in children and proper evaluation at an early stage can help improve the quality of life. The objective of the study was to assess the prevalence of ocular morbidity in school children. Methods: A cross-sectional study was conducted in 6 schools, which included Government and private schools around the field practice areas of a medical college. Eye examination was done which included testing for visual acuity, external examination and anterior segment examination with a pen torch and posterior segment examination with a direct ophthalmoscope. Statistical analysis: Data was analysed using SPSS. Results: Of the 402 children, 51.5% of the children were males and 48.5% were females. All the children were aged between 10 and 13 years. The most common eye symptom the students presented with was headache on reading for long durations (24.6%). The overall prevalence of ocular morbidity was found to be 20.4%. Refractive errors were the most common cause of ocular morbidity (14.2%). Parental history of wearing spectacles had an association with ptosis in children (p<0.026) and faulty near vision (p<0.022). Conclusions: Ocular morbidity is high in school going children. Since most of the causes of ocular morbidity are preventable or treatable, regular screening and early diagnosis and treatment can help improve the quality of life of children.